INTERPRETATION OF BEAUTY PRIVILEGE IN FILM (CASE STUDY OF RECEPTION ANALYSIS OF THE “BACKSTAGE” FILM) - Jocelyn, Jocelyn; Andriano, Stefanus; Hardika Widi Satria, Hardika Widi Satria (Jurnal Vokasi Indonesia, 2024)
The "Backstage" film is an Indonesian film that addresses the issue of beauty privilege wrapped in a drama genre. Beauty privilege often occurs in Indonesia, creating injustices in society. This film tells the story of two siblings pursuing their careers, but injustice occurs in terms of popularity due to the differences in appearance between Sandra and Elsa. The problem lies in the difference in treatment they receive based on their conformity to beauty standards. This study aims is to understand and analyze the meaning of beauty privilege as perceived by the audience after watching the film "Backstage". The theories used in this study are mass media theory, film theory, and reception analysis. This study employs a descriptive qualitative method using Stuart Hall's reception analysis. The data collection techniques used in this study are semi-structured interviews with five informants and observations. The research results indicate that four informants are categorized in the dominant-hegemonic position, one informant in the negotiated position, and no informants are categorized in the oppositional position. According to the informants, the "Backstage" film has well-represented the issue of beauty privilege, but one informant felt that the film's plot is still difficult to understand.